VIDEO CAPTURED LECTURES WITH SALAZAR’S METHOD OF GROUPING: EFFECTS ON STUDENTS’ ACHIEVEMENT IN DIFFERENTIAL CALCULUS - Salazar, Douglas Andag (Advances in Social Sciences Research Journal, 2016)
This study aimed to raise the achievement level of students in Differential Calculus using Video Captured Lectures with Salazar’s Method of Grouping. Using the quasi-experimental method of research, this study employed the qualitative and quantitative analysis relative to data generated by the Achievement Test and Math Journal with follow-up interview. Within the framework of the limitations of the study, the video captured lectures with enhanced groupings revealed a significant difference on the gain scores between the two groups and a significant difference within and between groups (control and experimental) on the student scores in the Achievement test. Although, the results revealed a failure mark on the pretest but a significant increase of the gain scores was achieved in the posttest. Specifically, an average increase was gained by the control group and a high increase was gained in the experimental group, credited to the actual video captured lectures. It is therefore possible to improve the student achievement level in Differential Calculus using the video captured lectures with Salazar’s Method of Grouping. Moreover, qualitative assessments showed that Salazar’s Method of Grouping creates and develops self-confidence, encourages effective communication and facilitates exchange of ideas towards a common goal. However, the students from the experimental group suggested in enhancing the actual video captured lectures in terms of audio and visual presentations.